Glutathione catalysis and the reaction mechanisms of glutathione-dependent enzymes - Deponte, Marcel (Biochimica et biophysica acta, 2013)
Background: Glutathione-dependent catalysis is a metabolic adaptation to chemical challenges encountered by all life forms. In the course of evolution, nature optimized numerous mechanisms to use glutathione as the most versatile nucleophile for the conversion of a plethora of sulfur-, oxygen- or carbon-containing electrophilic substances.